2013
DOI: 10.1007/s11250-013-0406-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brazilian red propolis administration on hematological, biochemical variables and parasitic response of Santa Inês ewes during and after flushing period

Abstract: Brazilian red propolis was administered orally to Santa Inês ewes, and evaluation was made of general health and hematological, biochemical, and parasitic responses during and after flushing. Thirty mature, nonlactating, nonpregnant Santa Inês ewes (40 ± 2 kg and 2.5 years old) were grazing tropical pasture (Brachiaria decumbens and Pennisetum purpureum) and, as flushing after synchronization, were supplemented with a concentrate-roughage mixture at a rate of 4 % body weight (BW). Ewes were divided according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 31 publications
4
29
0
3
Order By: Relevance
“…This red propolis presents new chemical substances (triterpenoids, isoflavonoids, prenylated benzophenones, and naphthoquinone epoxide) when compared to other samples (López et al, 2014;Morsy et al, 2013;Righi et al, 2011).…”
Section: Propolis Extracts Have Received Great Interest In Medicine Amentioning
confidence: 96%
“…This red propolis presents new chemical substances (triterpenoids, isoflavonoids, prenylated benzophenones, and naphthoquinone epoxide) when compared to other samples (López et al, 2014;Morsy et al, 2013;Righi et al, 2011).…”
Section: Propolis Extracts Have Received Great Interest In Medicine Amentioning
confidence: 96%
“…Recent studies mentioned to the general improvement of the animals health and immunity that fed propolis. The oral administration of ethanolic extract of Brazilian red propolis to Santa Inês ewes (3 g/ewe/day) during the flushing period increased total leukocytes, total protein and globulin concentrations, while decreased triglycerides, glutamate oxaloacetate transaminase, and glutamate pyruvate transaminase (Morsy et al, 2013). Hashem et al, (2013) found that the dietary ethanolic extract of the Egyptian propolis enhanced hematopoiesis including the number of red blood cells, hematocrite value and hemoglobin concentration.…”
Section: Effect Of Propolis On Blood Hematological Biochemical Parammentioning
confidence: 99%
“…Recently, numerous studies have proven the propolis activity against gram positive bacteria, viruses, fungi, oxidants, inflammation, tumors, parasites, protozoa and it may act against methanogenesis (Alencar et al, 2007;Aguiar et al, 2014;Morsy et al, 2013 and2015).…”
Section: What Is Propolis?mentioning
confidence: 99%
See 2 more Smart Citations